The en/gendering of volunteering: "I've pretty much always noticed that the tail runner is always female". Issue 3 (June 2020) - Stride, Annette; Fitzgerald, Hayley; Rankin-Wright, Alexandra; Barnes, Luke
Highlights: A volunteer centred perspective is critical to better understanding the place and meaning of volunteering in women's lives. Middle ground thinking enables a gendered analysis of women volunteers' experiences. Gender influences the volunteer experience - directly in the volunteering setting and indirectly in women's broader lives Sports organisations need to be more caring and interested in women volunteers' lives and circumstances. Abstract: The authors report on findings from part of a larger research project 'Gender in Volunteering Research' (GiVR). Data were collected from 24 women volunteers in 3 contexts—cycling, parkrun, and the broader field of leisure to explore the ways these women volunteer— including a consideration of the key challenges they face and how they overcome them. By taking a gendered analysis and drawing on feminist middle ground thinking, the authors extend current qualitative research within volunteering. Findings suggest the en/gendering of volunteering is evident within volunteer organisations through the ways in which gender influences the roles and volunteering experiences within these settings. Personal circumstances also mediate the en/gendering of volunteering and the women in this study were aware of how they needed to negotiate these so they could continue their volunteer activities. The authors highlight the need for sport organisations to be more caring and interested in their volunteers' lives and circumstances.